IMPLEMENTATION OF THE SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) SCIENCE LEARNING STRATEGY IN SMP NEGERI 10 PADANGSIDIMPUAN - Yuliani, Yuliani; Muttaqiin, Arief; Lestari, Tuti; Yurnetti, Yurnetti (Universe, 2025)
The rapid development of science and technology in the 21st century has increased awareness of the importance of education in developing individual competencies and improving overall educational quality. In Indonesia, educational quality remains a major concern. One contributing factor is the use of ineffective learning strategies, which often results in low student engagement and declining learning outcomes. Therefore, the selection of appropriate learning strategies is essential. The Survey, Question, Read, Recite, Review (SQ3R) strategy is one approach that can encourage students to participate actively in exploring, questioning, and discussing learning materials.This study aims to describe the implementation of the SQ3R strategy in science learning at SMP Negeri 10 Padangsidimpuan. A descriptive qualitative approach was used, involving 23 students from class VIII-1 as research participants. Data were collected through observations conducted during the learning process. The findings indicate that at the Survey stage, students successfully skimmed the material to gain an initial understanding, with an implementation rate of 100%. At the Question stage, students formulated relevant questions with a 98% implementation rate. During the Read stage, students read the material thoroughly, achieving 100%. At the Recite stage, they effectively recalled key concepts, also with 100%. Finally, at the Review stage, students were able to present their answers and review the material with a 99% implementation rate. Overall, the SQ3R strategy was implemented effectively, with an average implementation rate of 99%.